English article production in guided conversation by Afghan Dari EFL learners - Khoshgowar, Ahmad Nasim (Kansas State University, 2010)
The English article system is one of the most difficult and subtle structural elements for EFL learners, and even advanced learners make errors in article use. This research analyzes patterns of use of English articles (a/an, the, zero) in guided conversations with Afghan Dari speakers who are intermediate or advanced English learners and who do have an article system in their primary language, Dari. In this research, six intermediate and six advanced learners participated by discussing similar topics (their first impressions of the USA, their life in Manhattan, their classes, and their future plans). These conversations were recorded and transcribed. The collected data were analyzed on the basis of referentiality, information status, and various properties of nouns. The results indicate that the participants were most accurate in their production of the indefinite article ‘a/an’ in referential and non-referential contexts with new information, the definite ‘the’ in referential contexts with known information, while the zero ‘Ø’ was difficult for both ELP (intermediate) and Post-ELP (advanced) learners mostly in referential contexts.
Keywords: Production of articles by Afghan learners; Articles in guided conversation of Dari learners; Language, Linguistics (0290)